Global ethics : an introduction - Widdows, Heather, 1972- (Routledge/Taylor & Francis Group, 2014)
"Global ethics addresses some of the most pressing ethical concerns today, including rogue states, torture, scarce resources, poverty, migration, consumption, global trade, medical tourism, and humanitarian intervention. It is both topical and important. How we resolve (or fail to resolve) the dilemmas of global ethics shapes how we understand ourselves, our relationships with each other and the social and political frameworks of governance now and into the future. This is seen most clearly in the case of climate change, where our actions now determine the environment our grandchildren will inherit, but it is also the case in other areas as our decisions about what it is permissible for humans beings to do to each other determines the type of beings we are. This book, suitable for course use, introduces students to the theory and practice of global ethics, ranging over issues in global governance and citizenship, poverty and development, war and terrorism, bioethics, environmental and climate ethics and gender justice"--Provided by publisher